Model rozwoju pędu wierzchołkowego i jego ugałęzienia u dojrzałej brzozy omszonej (Betula pubescens Ehrh.) - Dmyterko, Elżbieta; Bruchwald, Arkadiusz (Leśne Prace Badawcze, 2010)
Preparation of the model of the terminal shoot development and its branching in mature hair birch based on the growth analysis and branching of the terminal bud, including relationships between different features, was the goal of this paper. In order to accomplish this goal, the following questions have had to be answered: from which auxiliary buds of the principal shoot epicormic shoots will grow, which of the epicormic shoots have the highest survival rate, which of auxiliary buds stay dormant, what is the number of epicormic shoots growing on the principal shoot? 310 annual increments of terminal shoots taken from 31 monocultures of hair birch stands, aging from 26 to 112 years, were examined as empiric material. The length of the principal shoot oscillated between 1–67 cm (22 cm in average) and was negatively (but not very strongly) correlated with the age of a tree ( r= 0,264). The annual principal shoot was built, in average, of 10 internodes (3–20). Between the number of internodes and the length of a shoot a clear relationship was found ( r= 0,826), the longer shoot consisted of a larger number of internodes. The average length of the internode of the principal shoot was 2,8 cm (0,3–5,5 cm) and was correlated with the length this shoot ( r= 0,717); longer shoots also presented longer internodes. In average 3,3 (0–14) epicormic shoots grew on the principal shoot. The highest number of epicormic shoots was found in 1998. The least number (skipping syleptic shoots occurred in 2000 – the year of measurement) was noted in 1996 and resulted from advanced natural process of drying of epicormic shoots. The strong relationship between the number of epicormic shoots and the number of internodes of the principal shoot was found (r=0,853). The largest probability of growing out of an epicormic shoot was in the case of the highest situated internode and the smallest probability was at the lowest one. The probability of the occurrence of the epicormic shoot was related to the length of the principal shoot and thus with the number of its internodes. The probability of mortality or damage of the principle shoot was related to the number of its internodes, too. The probability of dormancy of an auxiliary bud lowered with the distance of an internode from the base of a shoot.